Desterritorialização e reterritorialização das famílias da comunidade Deus é Amor com a construção da usina hidrelétrica de Belo Monte em Vitória do Xingu - AMORIM, Edilane Bezerra (Universidade Federal do Pará, 2023)
This dissertation discusses the transformations that took place in the Deus é Amor community, municipality of Vitória do Xingu, with the construction of the Belo Monte hydroelectric power plant, which, upon arriving in the territory, disrupted the socio-spatial organization of the families, in addition to causing a rupture with the place. and change the ways of life historically established by the subjects, contributing to the geographical movement Territorialization-Deterritorialization-Reterritorialization (TDR) in the Amazon. The community under study is part of what was demarcated by the hydroelectric project through the studies of the EIA-Rima (2009) as a rural Directly Affected Area, located in the sector referring to the Canals Reservoir. This area began to be occupied by families in the early 1980s, until 2011 had 59 families, and after the arrival of the Belo Monte HPP there were only 5 remaining families. The development of the research allowed the analysis of three central points about the object, the first with the understanding of the actions that made possible the territoriality of subjects in the Amazon (1970-2012), the second with the departure of the subjects from their historically constructed places, the deterritorialization (2011-2016) and finally the current process in which they are inserted, with the experience of progressive reterritorialization.